Strategies for Arabic Learning with a Formal Approach in the Disruption of the 21st Era - Al Usman, Semaun; Utami, Sri; Hayati, Istiqomatul; Daib Insan Labib, Muhammad Alfreda; bin Aman, Adham (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2023)
In essence, learning to master the language has significant achievements, as well as Arabic language learning. Ideally, Arabic language learning allows learners to master the four language skills (al-istimÄ', al-kalÄm, al-qirÄ'ah, and al-kitÄbah) functionally and proportionally. This approach considers language learning as a routine activity that is conventional and considered classical, following the usual ways of doing it based on experience. This study uses descriptive qualitative and several data sources by looking for literature references and documentation through manuscripts that follow the research. This research aims to discover that the era has entered the aspects of learning and teaching methods as a characteristic of the era of globalization. Science and technology are developing quickly and becoming increasingly sophisticated, with an increasingly broad role. 21st-century learning is a transition of learning where the curriculum developed leads schools to change the learning approach from teacher-centered to student-centered. It is following future demands where students must be able to think and learn by the demands of the times. These skills include problem-solving, critical thinking, collaboration, and communication skills so that the output from the old (traditional) strategy can still be used by prioritizing abilities centered on students. This study recommends future research to explore optimal ways of integrating artificial intelligence in Arabic language learning. Thus, this research contributes to the understanding and strategic application of advancing Arabic language learning in the Disruption 21 era.